Revising robotic surgery for stomach, potential benefits revised II: prevention of pancreatic fistula - Suda, Koichi; Nakauchi, Masaya; Inaba, Kazuki; Ishida, Yoshinori; Uyama, Ichiro (Translational Gastrointestinal Cancer, 2015)
Laparoscopic gastrectomy for gastric cancer has been widely accepted especially in early stages. It reduces postoperative pain, leading to faster recovery and shorter hospital stay, however, laparoscopically enhanced anatomy and improved hemostasis via pneumoperitoneal pressure have not contributed to reduction in early postoperative complications except for wound infection or improvement in long-term outcomes. Since 2009, we have been using robotic radical gastrectomy for operable patients with resectable gastric cancer, and have demonstrated that use of the robot particularly for proximal advanced gastric cancer attenuated early local complications including postoperative pancreatic fistula (POPF), leading to even shorter hospital stay. In this article, we present the current status and future perspectives on POPF following radical gastrectomy for gastric cancer focusing on the role of robotic gastrectomy in its prevention based on our experience and review of the literature.